Pengaruh Media Paper Toys Menggunakan Kertas Daun Pisang terhadap Kemampuan Motorik Halus Anak Usia Dini - Sari, Puja Nofila; Hazizah, Nur (Asian Journal of Early Childhood and Elementary Education, 2024)
This research is motivated by the fact that children's fine motor skills are not yet optimal, such as children's fine motor skills not being able to carry out movements that include small muscles with eye and hand coordination, for example folding, sticking, cutting, pinning and tying shoelaces. The purpose of this study is to gather data regarding the impact of banana leaf paper toys on young children's fine motor skills. In this study, experimental methodologies are combined with a quantitative methodology. All 115 students from the West Pasama Pembina State Kindergarten, who were split up into six classrooms, participated in this study. The testing method makes use of target samples, which are 15 kids from each of classes B2 and B1. The data collection process is carried out through the use of tests, and data analysis is carried out through normality, homogeneity, and hypothesis testing. The pre-test and post-test results for the experimental group averaged pre-test 13.2 and post-test 17.73. Meanwhile, the pre-test and post-test results for the control group were 12.6 and post-test 14. This difference occurred because of the paper toy activities carried out in the experimental class in this paper toy activity children used paper which we usually encounter in everyday life. such as using banana leaf paper which comes from nature, children usually only use origami paper and in this paper toy activity children not only fold, but here children will carry out folding, cutting, sticking, and producing 3-dimensional shapes, such as animal shapes, fruit, and other shapes using banana leaf paper.